Supplier Selection Decision Support System Drug Wighted Methods Product (WP) - Dina Fanita; Bosker Sinaga (Information Technology and Science (ITScience), 2020)
Supplier is very important for companies in services or goods, as well as parts procurement of medicines a Hospital, Hospital GrandMed is one of the largest hospital in Deli Serdang it's important to select suppliers for the procurement of drugs to be maintained and sustained quality of drug availabilitydrug and drug procurement logistics section to selectively choose a supplier with specific criteria so that the process of drug procurement at the Hospital GrandMed running properly and efficiently. The purpose of this study is to develop a decision support system to determine which is the best supplier priority Hospital medicine order so that can always keep the availability of drugs in terms of both the quality of medicines, price and delivery time. Data supplier in view of the historical kesupplier reservations about the company address, price, variants possessed drugs and drug quality and backed by the method of Weighted Product to support the decision which supplier to choose a priority determination. The results of this research program is to create a ranking and determination in the supplier selection GrandMed Hospital.Supplier selection decision support system with Weigthed method GranMed Product Hospital has been able to be built with UML and created with Visual Basic programming language in 2008.